2006
DOI: 10.1385/abab:134:2:155
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Escherichia coli Under Extremely Low-Frequency Electromagnetic Fields

Abstract: The influence of extremely low-frequency (ELF) electromagnetic fields on Escherichia coli cultures in submerse fermentation was studied. The fermentation processes were carried out recycling the culture medium externally through a stainless steel tube inserted in a magnetic field generator (solenoid). The exposure time and electromagnetic induction were varied in a range of 1 to 12 h and 0.010 to 0.10 T, respectively, according to a Box-Wilson Central Composite Designs of face centered with five central points… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 10 publications
1
34
1
1
Order By: Relevance
“…11 Therefore, in this work an extremely low-frequency electromagnetic field (ELF) was applied to an E. coli cell suspension during the fed-batch fermentation process to verify its influence on cell proliferation and recombinant gp41 protein production. The culture medium was recycled continuously through an external recycle loop coupled with a spiral U-shaped tube disposed inside the magnetic field generator.…”
Section: Introductionmentioning
confidence: 99%
“…11 Therefore, in this work an extremely low-frequency electromagnetic field (ELF) was applied to an E. coli cell suspension during the fed-batch fermentation process to verify its influence on cell proliferation and recombinant gp41 protein production. The culture medium was recycled continuously through an external recycle loop coupled with a spiral U-shaped tube disposed inside the magnetic field generator.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of electromagnetic field action in bacteria, several papers have reported alterations on growth, DNA molecules and gene expression Potenza et al 2004b;El May et al 2009). Escherichia coli cells exposed to an extremely low frequency magnetic field (0.1 T) for 6.5 h exhibited changes in viability compared to unexposed cells, which had a viability 100 times higher than the control (Justo et al 2006). El May et al (2009 reported that a static magnetic field (200 mT) induced a decrease of colony-forming units (CFU) of Salmonella enterica subsp.…”
Section: Introductionmentioning
confidence: 91%
“…A wide variety of responses involving magnetic field predominance have been summarized in Table 1. [6] AC MF 16, 60 Hz Enolase activity stimulation; Suppression of enolase activity [7] 0.05-1 mT Reduced transposition activity & enhanced cell viability [6] OMF 100 mT Exposure time dependent stimulation or inhibition of cell viability [8] 30 µT Cell density dependent changes in AVTD [9] DC EF NA Increase in growth, removal of inhibitory compounds in medium [10] AC MF 0. Growth increase and interestingly a loss of intercellular cohesion [16] Paper to be seen AC MF 0-0.3 Hz @ Elevated or even diminished growth rates for Bacillus subtilis, Candida albicans, Halobacterium, [17] 5−90 mT Salmonella typhimurium, and Staphylococci…”
Section: Group I: Treatments Involving Magnetic Field Predominancementioning
confidence: 99%